COMPARATIVE ANALYSIS OF THE IAPWS-IF97 FORMULATION PERFORMANCE FOR THERMODYNAMIC PROPERTIES OF WATER ON A RANKINE CYCLE - Fonseca Jr., J. G.; Schneider, P. S. (Revista de Engenharia Térmica, 2004)
The present paper presents the computational implementation of the industrial formulation of the thermodynamic properties of water at liquid and steam phases, proposed by the International Association for the Properties of Water and Steam, known as IAPWS-IF97. The validity field extends over to temperatures T between 0ºC and 800°C, for pressures p up to 100 MPa. Temperature T, specific volume v, specific enthalpy h, specific entropy s, specific heat at constant pressure cp and constant volume cv, besides saturation pressure ps, are calculated having a pair of known input values (p,T), (p,h) or (p,s). A comparative analysis between the IAPWS-IF97 routines and others, based on foregoing propositions, from an application on Rankine cycle, is made. IAPWS-IF97 has proved to be more precise, mainly because it accounts for the region of compressed liquid, besides requiring less processing time. The development is carried out as FORTRAN90 subroutines and functions and is available for public use according to a General Public License.